Performance assessment of hygrothermal modelling for diagnostics and conservation in an Italian historical church. (15th April 2021) - Frasca, Francesca; Verticchio, Elena; Cornaro, Cristina; Siani, Anna Maria
Abstract: The hygrothermal modelling of historical churches is a promising approach to study preservation issues and suitable retrofit measures. However, difficulties can arise in the use of Heat, Air and Moisture (HAM) models, which are often customised objects to be integrated into validated building energy simulation (BES). This research outlines a multi-step methodology to investigate the capability of a BES software coupled with a HAM model (BES + HAM) as a technique for diagnostics and conservation in complex settings. The 17th-century church of Santa Rosalia (Italy) was used as a historical site in a real context. As first step, the performance of the simulation tool was analysed through standardised exercises aiming at excluding incorrect assumptions and calculations in the HAM model (HMWall). Secondly, a building model of the church using a 1D heat transfer model (named building model A) was compared with one using HMWall (named building model B) in terms of the accuracy of the indoor climate simulations against hygrothermal measurements. The results showed that building model B enhanced the simulation accuracy by +50% with respect to building model A. Finally, annual simulations inside the church were run to further compare the seasonal trends of indoor climate scenario obtained from the two building models. Building model B allowed to study the water content distribution inside the altarpiece and a wall partition, showing that BES + HAM tools can be used to identify potential moisture-induced conservation risks. Highlights: The performance of HAM model in BES is evaluated through a multi-step methodology. Historical church walls are modelled using both heat transfer and HAM model in BES. Hygrothermal modelling using HAM enhances the accuracy of indoor climate simulation. HAM unlocks the chance to reliably evaluate conservation issues in historical walls.